How can we quarantine without a home? Responses of Activism and Urban Social Movements in Times of COVID‐19 Pandemic Crisis in Lisbon - Mendes, Luís (2020)
In Lisbon, during the COVID-19 pandemic period, new spaces for contestation and the action of urban social movements intensified, capitalising on the visibility for the right to housing, as a basic human right and an unconditional public health imperative, to fulfil the duties of lockdown and social isolation, imposed by the State of Exception. Its narrative and strategies reinforces the counter-hegemonic movement that denounces the logics of commodification and financialisation in the housing sector, placing hope in a post-capitalist transition in the post-COVID horizon. We conclude that the actors in this urban struggle have limited power over the changes they initiate, or make an effort to inflict, if they are not involved in a concerted and politically integrated action, not least because the achievements they obtain are temporary and exceptional, like the state of emergency imposed by COVID-19.